Covalent modification of nephrilin peptide with valproic acid increases its efficacy as a therapeutic in burn trauma. Issue 3 (July 2020) - Mascarenhas, Desmond D.; Ravikumar, Puja; Amento, Edward P.
Highlights: Immodulin peptides act as homeostatic rheostats in trauma models. Immodulins may modify the maturation, differentiation or polarity of monocytes. Valproic acid conjugation makes nephrilin peptide more efficaceous in burns. Nephrilins reduce sepsis mortality, kidney failure and burn trauma in rodents. Nephrilins are immodulins extended by a short sequence from Protor. Abstract: Introduction: Nephrilin peptide, a designed inhibitor of Rictor complex, modulates systemic responses to trauma, alleviating clinically relevant variables in a rat scald model and sepsis mortality in a mouse model. This study explores the possibility that chemical conjugation of small molecules to the aminoterminus of nephrilin can modify its biological activity in the rat scald model. Methods: One of four molecules (valproic acid, decanoic acid, fenofibric acid and ibuprofen) was chemically attached to the amino terminus of nephrilin during synthesis. Animals were treated with each modified nephrilin by subcutaneous bolus injection on days 1–7 post-burn. Results: Compared to nephrilin, valproic acid-modified nephrilin showed significantly (all p < 0.05) improved systemic effects on kidney function (creatinine 0.17 ± 0.03 vs 0.31 ± 0.09 mg/dL), glycemic control (AUC 57.5 ± 40 vs 136.4 ± 69.2 mg.dL.hr), inflammation (IL-6 24 ± 9 vs 39 ± 8 pg/ml), pathological angiogenesis (1.46 ± 0.87 vs 6.53 ± 3.16 pct pixels) and weight gain (3.74 ± 0.31 vs 2.99 ± 0.53 slope), all variables previously shown to bear upon clinically relevant burn injury outcomes. Conclusion: Modification of nephrilin with valproic acid increases the efficacy of nephrilin peptide in burns.